Pathogen-associated molecular patterns (PAMPs) derived from Leishmania and bacteria increase gene expression of antimicrobial peptides and gut surface proteins in sand flies - Vomáčková Kykalová, Barbora; Sassù, Fabiana; Dutra-Rêgo, Felipe; Soares, Rodrigo Pedro; Volf, Petr; Loza Telleria, Erich (International journal for parasitology, 2024)
The interaction between pathogens and vectors' physiology can impact parasite transmission. Studying this interaction at the molecular level can help in developing control strategies. We study leishmaniases, diseases caused by Leishmania parasites transmitted by sand fly vectors, posing a significant global public health concern. Lipophosphoglycan (LPG), the major surface glycoconjugate of Leishmania, has been described to have several roles throughout the parasite's life cycle, both in the insect and vertebrate hosts. In addition, the sand fly midgut possesses a rich microbiota expressing lipopolysaccharides (LPS). However, the effect of LPG and LPS on the gene expression of sand fly midgut proteins or immunity effectors has not yet been documented. We experimentally fed Lutzomyia longipalpis and Phlebotomus papatasi sand flies with blood containing purified LPG from Leishmania infantum, Leishmania major, or LPS from Escherichia coli. The effect on the expression of genes encoding gut proteins galectin and mucin, digestive enzymes trypsin and chymotrypsin, and antimicrobial peptides (AMPs) attacin and defensins was assessed by quantitative PCR (qPCR). The gene expression of a mucin-like protein in L. longipalpis was increased by L. infantum LPG and E. coli LPS. The gene expression of a galectin was increased in L. longipalpis by L. major LPG, and in P. papatasi by E. coli LPS. Nevertheless, the gene expression of trypsins and chymotrypsins did not significantly change. On the other hand, both L. infantum and L. major LPG significantly enhanced expression of the AMP attacin in both sand fly species and defensin in L. longipalpis. In addition, E. coli LPS increased the expression of attacin and defensin in L. longipalpis. Our study showed that Leishmania LPG and E. coli LPS differentially modulate the expression of sand fly genes involved in gut maintenance and defence. This suggests that the glycoconjugates from microbiota or Leishmania may increase the vector's immune response and the gene expression of a gut coating protein in a permissive vector.
Keywords: Mucins; Gastrointestinal Tract; trypsin; exprese genu; Innate immunity; gastrointestinální trakt; Glycosphingolipids; Insect Vectors; Gene Expression; Antimicrobial Peptides; zvířata; Membrane Proteins; Pathogen-Associated Molecular Pattern Molecules; Animals; Chymotrypsin; Bacteria LPS; chymotrypsin; Leishmania infantum; Psychodidae; antimikrobiální peptidy; Digestion; Gut protein; PAMP struktury; Lipopolysaccharides; hmyz - vektory; Insect Proteins; Trypsin; Female; Escherichia coli; glykosfingolipidy; ženské pohlaví; hmyzí proteiny; lipopolysacharidy; Lutzomyia; Leishmania major; Leishmania LPG; muciny; regulace genové exprese; Gene Expression Regulation; membránové proteiny; PAMPs; Phlebotomus